SISTEM INFORMASI GEOGRAFIS BANTUAN RUMAH LAYAK HUNI BERBASIS WEB PADA DINAS SOSIAL KABUPATEN BOLAANG MONGONDOW UTARA - Lasena, Marlin; Tambayong, Dedi (Teknosains: Media Informasi Sains dan Teknologi, 2016)
The aim of the research is to design a Geographic Information System Help Home Livable Web Based On Social Department North Bolaang Mongondow, the data collection process is expected to improve the effectiveness and efficiency of information on appropriate housing to the community. The method used in this research is descriptive method, is research which seeks to solve the problems that exist now systematically based on the existing data in a systematic, factual and accurate information on the facts, nature and the relationship between the phenomenon under study. To test this system using white box testing by selecting the modules of the web to be converted into a flowchart and then flow graph calculated after CC (Cyclometer Complexity) and Black box testing to obtain the test results are correct. Based on test results, we concluded that the Geographical Information System Web-Based Help Home Livable can improve the effectiveness and efficiency of the process of providing information on appropriate housing to the community.